THE MAIN TRENDS IN THE DEVELOPMENTOF WORLD ENERGY MARKETS - Mirzakhalilova Azizakhon Alisherovna (Scholar Express Journals, 2023)
The features of the formation of energy prices on a global scale are considered, the factors influencing this process are determined, the trends in the development of the world energy sector are analyzed, the reasons for their appearance are revealed. The article analyzes the forecast for the development of the world energy complex until 2030 by types of energy resources, and also provides an assessment of the state and prospects for the development of energy
Keywords: World energy markets; oil market; natural gas market; coal market